Analysis of wireless network usage at Universiti Utara Malaysia: a preliminary study towards bandwidth management - Shamsudin, Shahida; Katuk, Norliza; Abdullah, Kamarudin (2017)
The emergent of mobile device technology has increased the need for wireless network coverage in organizations. Users with mobile devices such as smartphones, computer tablets, and laptops require a wireless network to access the Internet services. Network administrators face challenges in managing access to the Internet and data usage by these devices. The challenge can be alleviated by implementing efficient bandwidth management strategies. Before identifying the proper strategies and implement them, network administrators must understand the usage pattern of the wireless network. Hence, this study presents an analysis of traffic pattern of wireless network usage by students at Universiti Utara Malaysia (UUM) as a preliminary input towards identifying the best strategies for managing wireless network bandwidth. The students' wireless network usage on a selected student residential area in UUM was analyzed for seven days using network management software. The data on the usage of protocols, service set identifiers, and types of applications were monitored and captured. The analysis of the data suggested valuable information towards managing bandwidth at the university.